User Experience Evaluation of Shopee-Based Product Sales at PT. Herba Hero Harmoni Using UEQ - Adira Arifandi; Melissa Putri Hutabarat; Lince Tomoria Sianturi; Chandra Frenki Sianturi (STMIK Methodist Binjai, 2026)
The development of digital technology encourages companies to use marketplaces as online sales and marketing channels. PT Herba Hero Harmoni uses the Shopee marketplace to support the sales of herbal products to customers. This study aims to evaluate the user experience of the online sales information system through the Shopee marketplace using the User Experience Questionnaire (UEQ) method. The study applied a quantitative descriptive approach involving 30 active Shopee users as respondents. Data were collected using the UEQ questionnaire, which consists of 26 items and six dimensions: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. The data were analyzed using the UEQ method and tested for validity and reliability. The validity test showed that 17 items were valid and 9 items were invalid. The reliability test obtained a Cronbach's Alpha value of 0.838, indicating that the instrument was reliable. The UEQ analysis showed average scores of 6.32 for attractiveness, 6.11 for perspicuity, 6.24 for efficiency, 6.05 for dependability, 6.38 for stimulation, and 5.96 for novelty. Stimulation achieved the highest score, while novelty achieved the lowest score but remained in the good category. Overall, the Shopee application provides a good to very good user experience and supports comfort, ease of use, and user satisfaction in online sales and purchase transactions.